Efficiency Testing of Pelton Turbines with Artificial Defects—Part 1: Buckets - Florian Fahrni; Thomas Staubli; Ernesto Casartelli (Energies)
Pelton turbines are susceptible to hydro-abrasive erosion from sediment-laden flows, resulting in a progressive loss of efficiency. Typical defect classes can be derived from the analysis of such damage observed in hydropower plants. A systematic strategy was developed to investigate the effect of locally damaged Pelton runners on the efficiency in laboratory tests using a model turbine. For this purpose, nine identical runners were fabricated and machined with an increasing size, depth, or number of different artificial defect types, such as splitter, rounded or sharp-edged, defects at the cutout, defects in the bucket base, and added ripples on the bucket sides. The processing steps, the efficiency measurement, and the extracted slopes of the efficiency drops are discussed in detail. The main findings are that the efficiency losses due to the various defects increase in a good approximation linearly with the machining depth and that the individual defect types can be superimposed. Defects at the splitter, bucket base, and bucket side dominate the losses at partial load of the turbine, while those at the cutout dominate at full load. Based on the results of this measurement campaign, power plant operators can estimate the magnitude of efficiency losses in their plant.